Maintenance standard at low cost flat / Azura Md Rasid - Md Rasid, Azura (2006)
Building is one of physical value asset and always need to maintain this building maintenance. It also happen at low cost flat although this occupant at this house are low -income group .In Malaysia low cost flat houses started for lower-income groups during The First Five-year plan from 1956 to 1960 to promote welfare of the Malaysians, especially the lower-income groups by providing improved housing, social and community services. During the Seventh Malaysian Plan (7MP, 1996 - 2000),the Government targeted to build 235,000 units of Low Cost houses to provide quality and affordable housing to all Malaysians and to improve quality of life for low-income groups especially the poor income. Maintenance management must take attention for the maintenance standard at low cost flat.